Comparison of blood loss and reduction of blood morphological values in patients undergoing pharmacological anesthesia during labor - Michalczyk, Michał; Torbé, Dorota; Torbé, Andrzej (Journal of Education, Health and Sport, 2018)
Aim: To assess and compare blood loss and reduction of blood morphological values in patients undergoing pharmacological anesthesia during labor.Material and methods: The study included 128 pregnant women ≥ 37 weeks, who were delivered vaginally.The women were divided into four groups:1. PCEA (n = 33) women giving birth under patient-controlled epidural anesthesia (PCEA) in a horizontal position; 2. Pethidine (n = 24) women giving birth subjected to analgesia by parenteral supply of pethidine; 3. Fentanyl (n = 25) women giving birth subjected to analgesia by parenteral supply of fentanyl; 4. Control (n = 46) women giving birth without analgesia. In each patient, in order to assess maternal blood loss during vaginal delivery, red blood cell (RBC) count, hematocrit (HT) value and hemoglobin (HGB) concentration before and after delivery, were assessed. Additionally, subjective evaluation of blood loss during delivery in milliliters, by a physician who assisted the delivery was performed.Results: A significantly greater decrease of maternal RBC-loss and greater decrease of HT-loss in the group of patients anaesthetized with pethidine in comparison to other groups was observed. There were no differences in the values of HGB-loss during labor between the study groups. Also the analysis of blood loss during delivery in milliliters, has not shown significant difference between the groups.Conclusion: Analgesia of labor with pethidine results in a significant reduction of the number of red blood cells and reduction of hematocrit values after delivery, in comparison to patient-controlled epidural anesthesia or analgesia with the use of fentanyl, as well as in comparison to the patients without any analgesia.